Existence of Cosplayers: A Study on Cosplayers Self-Disclosure through The Digital World of Instagram - Zahra, Kintania Ayunada Az; Kusuma, Arif Surya (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This research aims to analyze how cosplayers self-disclose via Instagram social media. This research is interesting to research because of the increasing popularity and openness of cosplayers holding their events in society where it used to be very rare to find cosplay events in the general public before Covid-19. Methodology: This research uses descriptive qualitative types and types with a positivism paradigm. Researchers used a purposive sampling technique to determine the data source. The informants used in this research were around 19 - 25 years old. The theory used is the self-disclosure theory of Joseph Luth and Harry Ingham (Johari Window). The data collection technique used in this research used observation and interviews. Data analysis refers to the Miles and Huberman model. The validity of the data uses triangulation from one information to another obtained through the interview. Results: The research results show that cosplayers' self-discovery through Instagram social media is divided into three categories, namely skills as self-expression, discomfort as social control and self-clarification. Applications/Originality/Value: This research seeks to find out how the self-disclosure process is analyzed using the quadrants of the Johari Window theory. The differences in this research include the object of research, the context used digital but using case studies instead of social, the recency of the place and research results.